Trustworthiness and Electrocortical Processing of Emotionally Ambiguous Faces in Student Police Officers - Sharif, Limi (Psychiatry Res Neuroimaging, 2020)
Perceptions of emotional facial expressions and trustworthiness of others guides behavior and has considerable implications for individuals who work in fields that require rapid decision making, such as law enforcement. This is particularly complicated for more ambiguous expressions, such as ‘neutral’ faces. We examined behavioral and electrocortical responses to facial expressions in 22 student police officers (18 males; 23.2 ± 3.63 years). Participants completed an emotional face appraisal task that involved viewing three expressions (fearful, neutral, happy) and were asked to identify the emotion and rate the trustworthiness of each face. The late positive potential (LPP), an event-related potential that tracks emotional intensity and/or salience of a stimulus, was measured during the task. Overall, participants rated neutral faces similarly to fearful faces and responded fastest to these expressions. Neutral faces also elicited a robust late LPP response that did not differ from LPP to fearful or happy faces, and there was substantial individual variation in trustworthiness ratings for neutral faces. Together, ‘neutral’ facial expressions elicited similar trustworthiness ratings to negatively-valenced stimuli. Brain and behavioral responses to neutral faces also varied across student officers; thus, encounters with ambiguous faces in the field may promote increased perceived threat in some officers, which may have real-world consequences (e.g., decision to shoot, risk of psychopathology).